Analisis Finansial dan Strategi Pengembangan Usaha Budidaya Ikan Kerapu (Epinephelus sp) di Kecamatan Mantang Kabupaten Bintan - Handayani Handayani; Zulkarnaini Zulkarnaini; Syafriadiman Syafriadiman (Berkala Perikanan Terubuk, 2015)
The research was conducted from May to July 2014 in Mantang district, Bintan regency. The object of this research were to evaluate the feasibility level based on financial and sensitivity aspects, contribution to local revenues and to formulate alternative strategies. This research used survey method. The result shows that the business of groupers floating cages in Mantang district was feasible and profitable. Contribution of business groupers was lesses to local revenues Bintan District. The combination score of external, internal matrix indicates that the position of the business in growth strategies. SWOT analysis find out of four alternatives strategies to increase production and development business.